BINA-DAMAI DALAM KOMUNITAS PESANTREN: SEBUAH UPAYA COUNTER-RADIKALISME - Mantu, Rahman (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
This article discussed about the experience of al-Qodir Boarding School in Sleman Yogyakarta in the effort to counter the radicalism through the approach of peace building. Applying qualitative approach, this research using the methods of observation and deep interview in collecting data. With the theoritical framework of cognitive peace building, three factors of peace building became the focus; the mechanism of internal group, among group and external group. The main research finding here was the essential role of kiai in building participative dialogue with the community out of the boarding school which was implemented through social actions. It resulted in the ability of al-Qodir Boarding School in formulating the strategy of radicalism counter which became a typical strategy of pesantren among so many strategies to find out new formulations in avoiding the movement of radicalism in Indonesia.***Tulisan ini akan membahas tentang pengalaman Pondok Pesantren Al-Qodir terhadap upaya counter-radikalisme melalui pendekatan bina-damai di Sleman Yogyakarta. Penelitian ini menggunakan metode kualitatif dengan melakukan pengamatan serta wawancara mendalam. Kerangka teoritik yang digunakan peneliti adalah teori peace building. Perdamaian menurut teori ini bisa tercipta karena tiga faktor; mekanisme internal, antar kelompok dan eksternal. Temuan dari riset ini adalah adanya peran penting kiai dalam membangun dialog partisipatif dengan masyarakat luar pesantren yang terimplementasi melalui aksi-aksi sosial. Hasilnya Pesantren Al-Qadir mampu merumuskan strategi counter-radikalisme yang khas pesantren ditengah upaya banyak pihak mencari formulasi baru dalam menangkal gerakan radikalisme di Indonesia.